Trump’s Middle East tour: Status quo reset - Rich, Ben (2017)
President Donald Trump’s upcoming Middle East tour, his first international trip since assuming office in January, will take him to the heart of the three monotheistic faiths, beginning in Saudi Arabia, travelling to Israel and finishing at the Vatican. The symbolism of the tour is manifold. Perhaps most importantly though, it is an insight into Trump's international priorities. While much of Obama’s foreign policy thinking was focused on Asia, with a goal of containing a rising China, Trump’s first major sojourn abroad may suggest a prioritisation of the Middle East. The choice and hierarchy of locations is also telling. The fact that Trump has selected both the Saudi kingdom and the Jewish state in the same trip has raised more than a few eyebrows. To maintain a sense of diplomatic neutrality, US presidents have typically tried to avoid contiguous visits to Israel while touring Arab states. In line with previous behaviour, his itinerary suggests Trump has little regard for such delicate nuances.